Global screening of health behaviors: Introducing Lev-screening (Lev-s)-development and psychometric evaluation. - Douglas Sjöwall; Felicia Stålhand; Greta Schettini; Petter Gustavsson; Tatja Hirvikoski (PLoS ONE)
Poor health behaviors have been identified as a critical factor for the burden on healthcare systems and individual suffering. However, comprehensive assessment of health behaviors is time-consuming and often neglected. To address this, we introduce the Lev-screening (Lev-s), a new, brief tool that covers multiple health behaviors. The Lev-s assesses ten health behaviors-physical activity, diet, alcohol use, tobacco use, illegal drug use, sleep, social relations, meaningful activities, sexual health, and screen health-using 33 items. This article details the development and psychometric evaluation of Lev-s with a sample of 2,279 participants aged 18-87. Test-retest reliability estimated as intra-class correlation coefficients for the different health behaviors ranged from .71 to .98 (n = 157), indicating moderate to excellent reliability. Lev-s showed associations with quality of life, demonstrated inter-correlations among included health behaviors, and detected group differences between individuals with and without neurodevelopmental conditions. The Lev-s exhibits satisfactory psychometric properties and holds promise as an efficient tool for screening of health behaviors.